Elements for successful implementation of a clinic-based health literacy intervention - Macauda, Mark M.; Arent, Michelle A.; Sakhuja, Mayank; Yelton, Brooks; Noblet, Samuel; Fedrick, Delores; Zona, Diana; New, Cyndi; Isenhower, William D.; Wandersman, Abraham; Friedman, Daniela B. (Frontiers in Public Health, 2022)
Improving health literacy is a national public health priority. Given the context of the Covid-19 pandemic, it is even more critical for health and medical information to be clear and understandable for patients and their families. Clinic-based programs to improve health literacy need to be pragmatic, feasible, and helpful for the implementing clinic and patients. This paper describes the development, implementation, and evaluation of a pragmatic, clinic-based health literacy intervention in a safety-net clinic that serves uninsured and indigent patients. Study methods are guided by a previous pilot study and components recommended for pragmatic interventions. An electronic readiness assessment was distributed to out-patient clinics affiliated with a statewide hospital association. The AskMe3 tool was used for the intervention as it is evidence-informed and relatively easy to implement. Implementation included ongoing dialogue between the clinic and the academic research team. Within the implementing clinic, data collected from patients via verbally administered questionnaires was analyzed using descriptive statistics and chi-squares. Interview data collected from the clinic director was analyzed qualitatively for themes. The implementing clinic had some of the lowest average scores of the 34 clinics who participated in the initial readiness assessment. Despite this, they were able to successfully implement the health literacy intervention during a global pandemic. Eighty-eight participants completed patient questionnaires at this clinic. Most patients (96%) agreed the AskMe3 questions helped them talk with the doctor or nurse at their current appointment. Most (99%) also perceived the AskMe3 tool to be very helpful when used in a clinical setting. The clinic director offered that the staff initially thought the intervention would be difficult to implement. However, implementation by clinic volunteers with encouragement and prioritization of health literacy by the clinic director contributed to success. When considering interventions for clinical settings, a pragmatic approach can help with selection and implementation of a program that fits with the realities on the ground. Further, frequent technical assistance can help resolve implementation barriers. Interventions utilizing tools such as AskMe3, because of their simplicity, allow creative solutions to capacity issues for clinics who see a need for health literacy improvements.